Electronic banking and treasury security - Welch, Brian (Boca Raton, FL : CRC Press : Woodhead Pub. and the Association of Corporate Treasurers, 1999)
This edition takes into account the very latest advances in electronic banking and treasury security. The electronic transmission of funds from companies to banks means that companies are responsible for high levels of risk previously covered by the bank's own security systems
Rev. ed. of: Electronic banking and security. 1994.
Includes index.
oif 18/07/14
Loan
Keywords: Electronic funds transfers; International business enterprises; Treasury management